DYNAMICS OF SPATIAL ABUNDANCE OF ZOOPLANKTON IN MORELLA COASTAL WATERS, CENTRAL MALUKU - Hanung Agus Mulyadi; Abdul Wahab Radjab (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
The dynamics abundance of zooplankton in Morella coastal waters is poorly known.The purpose of this study was to detemine the abundance of zooplankton in Morella coastal waters during Southeast Monsoon. This research was conducted in August 2011. Plankton samples were collected from five stations, by NORPAC net that was vertically hauled from 10 meter depth up to the surface (except in Station 5, less than 10 m). The result showed that composition of zooplankton in Morella consisted of 43 taxa of zooplankton (33 taxa of holoplankton and 10 taxa of meroplankton). Total abundance of zooplankton was between 752 and 1050 ind/m3 (average 890±128 ind/m3), which was dominated by Copepods (53.70%). The abundace of the Copepods was between 368 and 742 ind/m3 (average 481±153 ind/m3). Copepods that typically found in coastal water may have higher tolerant on oceanographic factors than one that typically found in oceanic water. Sagitta enflata was identified as the most abundant, followed by Oncaea sp and Acrocalanus gibber. Echinoderms larvae were abundant in the pluteus stage (8 arms) indicated that spawning process occurred in August. The Bray-Curtis clustering analyses showed that in station 4 there were six different species zooplankton indentified in this location. Keywords: structure community, copepods, meroplankton, chaetoghnata, Morella